Diversity of Polychaetes in Mangrove Forest, Prasae Estuary, Rayong Province, Thailand - Somtawin Jaritkhuan (Science Faculty of Chiang Mai University, 2019)
The study on diversity, density and biomass of polychaete worm in mangrove forest at Prasae estuary, Rayong Province, Thailand were conducted by 2 collections of samples, dry season (February 2013) and wet season (July 2013). There were 3 stations, namely, the Marine Resource Development and Eastern Thai Coast Research Centre (P.1), Prongtong field (P.2) and Loy Island (Koh-Loy, P.3). Ten families with 27 genera were identified by which Family Capitellidae (Capitella sp. and Dasybranchus spp.), Family Nereidae (Namanlycastic sp.) were frequently found with dominated by Capitella sp. The average density, biomass, species diversity index, species richness, and an evenness index between the dry and wet season were 79.82±30.24 ind/m2, 0.62±0.29 g/m2, 1.39±0.70, 2.41±1.29, and 0.91±0.05, respectively. The similarity index with cluster analysis of polychaetes at different sub-stations during dry and wet season using Bray-Curtis similarity could be separated into 4 main groups at 80%.